2020
DOI: 10.3389/fneur.2020.533375
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Thickness and Microvascular Pattern in Early Parkinson's Disease

Abstract: A thinning of intraretinal layers has been previously described in Parkinson's disease (PD) patients compared to healthy controls (HCs). Few studies evaluated the possible correlation between retinal thickness and retinal microvascularization. Thus, here we assessed the thickness of retinal layers and microvascular pattern in early PD patients and HCs, using, respectively, spectral-domain optical coherence tomography (SD-OCT) and SD-OCT-angiography (SD-OCT-A), and more interestingly, we evaluated a possible co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
5
30
3
2
Order By: Relevance
“…They found that the retinal capillary skeleton and perfusion densities and capillary complexity of SCP were significantly lower in PD patients than in healthy controls ( Shi et al, 2020 ). Unlike our results, in the study by Rascunà et al (2020) no significant difference in microvascular density was observed between PD patients and healthy controls. These results were variable and inconsistent, possibly due to the study design, and patient selection.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that the retinal capillary skeleton and perfusion densities and capillary complexity of SCP were significantly lower in PD patients than in healthy controls ( Shi et al, 2020 ). Unlike our results, in the study by Rascunà et al (2020) no significant difference in microvascular density was observed between PD patients and healthy controls. These results were variable and inconsistent, possibly due to the study design, and patient selection.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we found that the decrease in FAZ area was accompanied by an increase in microvascular parameters in the foveal zone, like skeleton and perfusion density, fractal dimension or lacunarity. This contrasts with the results of Zou et al who found less vessel length and perfusion in the central macula of PD patients and no changes in FAZ area ( Zou et al, 2020 ), and with the results of Rascunà et al who did not find vascular density changes in the foveal zone of early PD patients ( Rascunà et al, 2020 ). Some of these differences might be attributed to smaller sample sizes, differences in disease stage of patients and study design flaws of previous studies.…”
Section: Discussioncontrasting
confidence: 97%
“…Studying the morphometric variations of capillary networks in PD might provide key information about the regional neuronal structure, and the basis for investigating retinal vascular morphological features as potential biomarkers of cerebral microcirculation in PD. Although to date few studies have explored retinal vascular alterations in PD using OCT-A, the observations so far support the view that retinal vascular alterations are present in PD (Kromer et al, 2016;Kwapong et al, 2018;Rascunà et al, 2020;Shi et al, 2020;Zou et al, 2020;Robbins et al, 2021).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Optical Coherence Tomography Angiography of the macula was carried out employing AngioVue XR Avanti (Optovue Inc, Fremont, California, United States) after pupil dilation with 1% Tropicamide. The technology of OCTA has been previously described in detail ( Querques et al, 2016 ; Moghimi et al, 2018 ; Bonfiglio et al, 2019 ; Rascunà et al, 2020 ). The rate of A-scan was 70,000 per second and the bandwidth was 50 nm.…”
Section: Methodsmentioning
confidence: 99%